Analysis Of The Influence Of Tiktok Content Marketing, Online Customer Review, Product Quality On Product Buying Interest Sunscreen Facetology (Case Study of Students of the Faculty of Economics and Business, Universitas Kristen Indonesia) - Fista Basani Rajagukguk; Carolina F Sembiring; Ganda T Hutapea (Universitas Kristen Indonesia, 2026)
This research focuses on three independent variables Content Marketing via TikTok, Online Customer Reviews, and Product Quality to analyze their influence on Buying Interest toward Facetology sunscreen products. The study subjects are limited to students of the Faculty of Economics and Business, Universitas Kristen Indonesia (FEB UKI). Data were collected by distributing questionnaires to 75 respondents selected through purposive sampling. The methodology adopts a quantitative approach as the basis for data collection and processing, with a series of analyses including validity and reliability tests, followed by classical assumption tests to verify the feasibility of the regression model, and further analyses such as: 1) multiple linear regression, 2) coefficient of determination (R²), and 3) hypothesis testing (t-test and F-test). The hypothesis test results show that Content Marketing does not have a significant partial influence on Buying Interest, with a significance value of 0.342, exceeding the 0.05 threshold. Online Customer Reviews are proven to have a significant influence, with a significance value of 0.010, which is below 0.05. The Product Quality variable also contributes significantly to Buying Interest, with a significance value of 0.001, reinforcing the assumption that perceptions of product quality play a major role in buying interest. The F-test results also indicate that all three independent variables jointly have a significant influence on the Buying Interest for Facetology sunscreen products. Therefore, the combination of content promotion, online customer reviews, and product quality collectively becomes an important factor driving consumer interest specifically FEB UKI students for purchase the product under study. Keywords: Content Marketing, Online Customer Review, Product Quality, Buying